Micro and nanocrystalline cellulose fibre-reinforced jatropha oil-based polyurethane composite films - Osman Al Edrus, Syeed Saifulazry (2017)
One of the major drawbacks of using neat bio-based polymer is its poor mechanical properties. Since ancient, cellulose fibres always become preferable reinforced material to enhance mechanical properties esspecially for composite products. Number of studies on polyurethane and polyol from jatropha oil for various applications have been carried out, but none of it incorporating cellulose fibre as a reinforcement material. In this study, composite films from jatropha oil-based polyurethane (JOPU) reinforced with microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC) fibres were prepared using film casting method. JOPU was produced by reacting jathropha oil polyol and reacts with 4,4’-diphenyl-methane diisocyanate (MDI). Dimethylformamide (DMF) was used as solvent to disperse MCC and NCC fibres prior to mixing with JOPU. Different fibre loadings ranging from 2.5 to 10 wt. % for MCC, and 0.10 to 1.50 wt. % for NCC were used. The average size of MCC and NCC used in this study were 112.3 μm and 180.82 nm for length and 21.4 μm and 11.29 nm in diameter respectively. Thermogravimetric analysis shows that NCC has lower thermal stability than MCC. The crystallinity index (CI) of cellulose was decreased from 85.3% in the form of MCC to 78.0% after being reduced to NCC. Composite films made from JOPU/MCC and JOPU/NCC mixtures were successfully produced. The addition of MCC was not affected the colour but had increased density, reduced transparency and roughened surface morphology of JOPU/MCC films. In contrast with for JOPU/NCC films, only the colour of the films was affected changing from bright golden-yellowish to darker golden-yellowish colour. Effects on other properties were marginal. FTIR spectroscopy shows typical polyurethane spectra for all films indicate addition of MCC and NCC not affect much on chemical properties of the films. The thermal stability of JOPU film (Tg, 5.05 °C) was found reduced with addition of fibres with Tg range of 3.72 to -2.31 °C for JOPU/MCC films and 2.14 to -0.97 °C for JOPU/NCC films. The tensile strength for JOPU/MCC and JOPU/NCC films were increased from 54 to 356 % and 132 to 229 % respectively. For tensile modulus, increment were recorded from 49 to 2366 % and 173 to 653 %, respectively. In contrast, elongation at break appears to be dramatically declined from 340 % for JOPU to as low as 54 % in JOPU/MCC films and 124 % in JOPU/NCC films. Both water wettability and water uptake properties found increased as the content of MCC and NCC increased. Rapid wettability was recorded in less than 10 sec. esspecially in JOPU/NCC films. However the water uptake after 5 days soaking shows plateau trend at 3 to 5% for JOPU/NCC films compared to JOPU/MCC films which shows increasing trend 4 to 16 %. As overall conclusion, the addition of cellulose fibres (esspecially NCC) even at low amount in JOPU-based films had succesfully enhanced mechanical properties; tensile strength and modulus, and shows minimal effects on physical properties of the films. However, other properties; thermal stability, elongation at break, water wetabillity and water uptake, found significantly affected.